Treatment of intestinal Behçet's syndrome with chimeric tumour necrosis factor α antibody. Issue 5 (1st November 2001) - Travis, S P L; Czajkowski, M; McGovern, D P B; Watson, R G P; Bell, A L
Abstract : Few patients with Behçet's syndrome have gastrointestinal ulceration. Such patients are difficult to treat and have a higher mortality. Faced with refractory symptoms in two patients with intestinal Behçet's, we used the tumour necrosis factor α (TNF-α) monoclonal antibody infliximab to induce remission. Both women (one aged 27 years, the other 30 years) presented with orogenital ulceration, pustular rash, abdominal pain, bloody diarrhoea due to colonic ulceration, weight loss, and synovitis. One had thrombophlebitis, digital vasculitis, perianal fistula, and paracolic abscess; the other had conjunctivitis and an ulcer in the natal cleft. Treatment with prednisolone, methyl prednisolone, and thalidomide in one and prednisolone, colchicine, and cyclosporin in the other was ineffective. After full discussion, infliximab (3 mg/kg, dose reduced because of recent sepsis in one, and 5 mg/kg in the other) was administered. Within 10 days the ulcers healed, with resolution of bloody diarrhoea and all extraintestinal manifestations. A second infusion of infliximab was necessary eight weeks later in one case, followed by sustained (>15 months) remission on low dose thalidomide. Remission was initially sustained for 12 months in the other but thalidomide had to be stopped due to intolerance, and a good response to retreatment lasted only 12 weeks without immunosuppression, before a third infusion. The cause of Behçet's syndrome is unknown but peripheral blood CD45 γδ T cells in Behçet's produce >50-fold more TNF-α than controls when stimulated with phorbol myristate acetate and anti-CD3. Infliximab could have a role for inducing remission in Behçet's syndrome.